THE IMPACT OF INFLAMMATION ON DIABETES: PHYSIOLOGICAL PATHWAYS AND CLINICAL OUTCOMES - Sahib Abdulhasan, Rawaa (PT. Antis International Publisher, 2025)
Objective: To investigate the role of inflammation in diabetes, its impact on physiological pathways, clinical outcomes, and potential therapeutic strategies. Methods: A comprehensive review of existing literature was conducted to elucidate the mechanisms linking inflammation with diabetes and evaluate the clinical implications and emerging therapeutic approaches. Results: Inflammation significantly contributes to the onset and progression of diabetes. In type 2 diabetes, chronic low-grade inflammation, driven by pro-inflammatory cytokines like TNF-α and IL-6, disrupts insulin signaling, leading to insulin resistance. Oxidative stress induced by inflammation further deteriorates beta-cell function, impairing insulin production. In type 1 diabetes, autoimmune-induced inflammation destroys pancreatic beta cells, triggering hyperglycemia. Clinically, elevated markers such as CRP are correlated with complications like cardiovascular diseases, neuropathy, and nephropathy. Anti-inflammatory therapies show promise in improving glycemic control and reducing complications. Novelty: This study highlights the intricate link between inflammation and diabetes, emphasizing novel therapeutic strategies targeting inflammation to address glycemic control and mitigate disease-related complications. Understanding these mechanisms is essential for combating the global diabetes epidemic.